Cost of cancer management by stage at diagnosis among Medicare beneficiaries. (3rd August 2022) - Reddy, Sheila R.; Broder, Michael S.; Chang, Eunice; Paydar, Caleb; Chung, Karen C.; Kansal, Anuraag R.
Abstract: Objective: Estimate the annual cost of care in the 5 years following a cancer diagnosis for 17 invasive cancer types, by stage at diagnosis. Methods: We used 2012–2016 data from the Surveillance, Epidemiology, and End Results (SEER) registry-Medicare claims database to examine cost of care among Medicare beneficiaries with a confirmed cancer diagnosis based on International Classification of Diseases for Oncology, Third Edition histology codes reported in SEER. Beneficiaries contributed to the annual cost calculations (Years 1–5) using their observed time after diagnosis. Beneficiaries were continuously enrolled in fee-for-service Medicare Parts A/B and Part D during follow-up. Total, inpatient, outpatient, and pharmacy cancer-related service costs were calculated. Results: From 2012 to 2016, we identified 597, 778 Medicare beneficiaries with incident cancer diagnosis within 5 years (Stage I, II, III, and IV: 32.6%, 33.4%, 15.9%, and 18.0%, respectively). In Year 1, mean (standard deviation) total costs for Stage I diagnoses varied from 7640 (17, 378) (prostate) to 94, 636 (117, 636) (pancreas). Total costs increased by stage and reached 58, 783 (92, 344) (prostate) to 156, 982 (175, 009) (stomach) for Stage IV diagnoses in Year 1. Costs in Year 1 were significantly higher for Stage IV diagnoses than for earlier stages across all cancer types. In Years 2–5, total costs were lower than in Year 1 but continued to increase by stage. Conclusions: Beneficiaries diagnosed at later stages of cancer have higher costs of care (up to 7 times as much) than those diagnosed at earlier stages. Earlier cancer diagnosis may lead to more efficient treatment and decreased management cost.